THE ROLE OF SMALL BUSINESS AND ENTREPRENEURSHIP IN MAHALLA (World Economics and Finance Bulletin, 2022)
Entrepreneurship plays a major role in solving existing problems in the social and economic spheres in the society and in the socio-economic development of the society. It creates new jobs in the fields of production, work performance, and service, and is of great importance in providing employment to the population and reducing unemployment. More than half of the new jobs created every year both in developed countries and in Uzbekistan belong to small and private businesses
Keywords: Economic spheres; Unemployment; population; Business entities